Legal Implications of Notarial Deed Signing Reading Not Carried Out Simultaneously by the Parties Before a Notary Public PPAT - Kusuma Putra, Erico Setyawan; Shallman, Shallman (TABELLIUS: Journal of Law, 2025)
Abstract. The form and procedures stipulated by Law No. 2 of 2014 concerning the Position of Notary and Regulation Order 24 of 2016 concerning the Land Deed Making Official are clear, however, there is a Reading and Signing of Notarial Deeds that are not carried out simultaneously by the Parties in the presence of the Notary and the Land Deed Making Official, so the author would like to describe the Legal Implications in the Reading and Signing of Notarial Deeds that are not carried out simultaneously by the Parties in the presence of the Notary and the Land Deed Making Official and their Responsibilities. The writing method uses a normative legal approach in order to obtain the conclusion that the Notary Position Law, Government Regulation concerning the Land Deed Making Official and other regulations have regulated it well, both implicitly and explicitly. Thus, the results of the discussion obtained are as follows: (1) Authentic Deeds are closely related to the obligations and sanctions given to Notaries. Notaries are authorized to make authentic deeds as regulated in Article 15 of Law No. 2 of 2014 concerning the Position of Notaries. Notaries in carrying out their authority have obligations that must be carried out as regulated in Article 16 paragraph (1) letter I and paragraph (8). Where if it is not fulfilled, its authenticity will be lost unless there is an obstacle in accordance with Article 44 paragraph (1) while in the Regulation of Order 24 of 2016 concerning Land Deed Making Officials, the authority is contained in Article 2 which has obligations that must be carried out in accordance with Article 22. The legal implication is that it can be canceled or null and void by law because it does not meet the subjective requirements in the form of an agreement between the parties and the objective requirements in the form of a lawful cause. In addition, the making of a deed which contains a procedure that is not in accordance with the making of the deed results in the deed being formally defective (2)if provencan be dismissed dishonorably for not carrying out his duties and position properly.and civil and criminal sanctions may be imposed depending on how much the negligence causes losses to the parties.Keywords: Land Titles Registrar; Notary Public; Reading and Signing.